Virus-specific read-through codon preference affects infectivity of chimeric cucumber green mottle mosaic viruses displaying a Dengue Virus epitope - Teoh, P.G.; Ooi, A.S.; AbuBakar, Sazaly; Othman, R.Y. (Hindawi Publishing Corporation, 2009)
A Cucumbergreen mottle mosaic virus (CGMMV) was used to present a truncated dengue virus type 2 envelope (E) protein binding region from amino acids 379 to 423 (EB4). The EB4 gene was inserted at the terminal end of the CGMMV coat protein (CP) open reading frame (ORF). Read-through sequences of TMV or CGMMV, CAA-UAG-CAA-UUA, or AAA-UAG-CAA-UUA were, respectively, inserted in between the CP and the EB4 genes. The chimeric clones, pRT, pRG, and pCG+FSRTRE, were transcribed into full-length capped recombinant CGMMV transcripts. Only constructs with the wild-type CGMMV read-through sequence yielded infectious viruses following infection of host plant, muskmelon (Cucumis melo) leaves. The ratio of modified to unmodified CP for the read-through expression clone developed was also found to be approximately 1: 1, higher than what has been previously reported. It was also observed that infectivity was not affected by differences in pI between the chimera and its wild counterpart. Analysis of recombinant viruses after 21-days-postinculation (dpi) revealed that deletions occurred resulting in partial reversions of the viral population to near wild type and suggesting that this would be the limiting harvest period for obtaining true to type recombinants with this construct. Copyright (c) 2009 Pak-Guan Teoh et al.